Radiological and histological comparison between nano-bioglass and commercial bioglass in bone healing in a rabbit model. (January 2016) - Dehkordi, Saeed; Bigham-Sadegh, Amin; Karimi, Iraj; Momeny, Majid; Balali-Dehkordi, Shima; Bafghi, Mehdi; Amini-Khoei, Hossein
Abstract Fracture healing is a complex physiological process. It involves the coordination of several different types of cells, proteins, and expression of various genes. Bone healing is very essential for fracture management, malfusion, osteomyelitis, removal of bone tumors, joint attachment, and also in joint prothesis. Diverse synthetic and biological grafts are used in bone healing. In this study, we evaluated and compared the effects of nano-bioglass and commercial bioglass on healing of experimental tibial defects in ten white New Zealand rabbits. Three round holes were created in tibial bone with orthopedic drill. One of the hole was left empty as control while the other two holes were filled by experimental grafts. Radiografts were taken after 2 and 6 weeks whereas pathological slides were prepared only after 6 weeks. Radiological and histological evaluation was performed blindly, and the results score were analyzed statistically. The data showed that nano-bioglass is superior to commercial bioglass in bone healing whereas commercial bioglass is better than control.